Creatine supplementation - Lulinski, B.
Creatine is marketed as "nature's muscle builder" and "the most legitimate sports supplement around." Professional and amateur athletes alike are gobbling up this alleged ergogenic aid, hoping to increase their strength and performance. Creatine supplementation is claimed to increase muscle power by playing a role in the transfer of energy to help the muscle contract. Supplement labels state that "creatine is converted to phosphocreatine, which is important for short energy bursts such as sprinting and weight lifting" and that "depletion of phosphocreatine can result in muscle fatigue and fading muscle power." Claims are also made that supplementation increases muscle body mass. eferences 1. Murray RK and others.. Harper's Biochemistry, 24th Edition. Stamford, CT: Appleton & Lange, 1996. 2. Sahelian R, Tutle D. Creatine: Nature's Muscle Builder. Garden City, NY: Avery Publishing Group, 1997. 3. Toler S. Creatine is an ergogen for anaerobic exercise. Nutrition Reviews 55:21-25, 1997. 4. Maughan R. Creatine supplementation and exercise performance. International Journal of Sport Nutrition 5:94-101, 1995. 5. Harris RC, Soderlund K, Hultman E. Elevation of creatine in resting and exercised muscle of normal subjects by creatine supplementation. Clinical Science 83:367-374, 1992. 6. Haff GG, Potteiger JA. Creatine supplementation for the strength/power athlete. Strength and Conditioning 19(6):72-74, 1997. 7. Coleman E. Creatine monohydrate: a sprint performance enhancer? 8. Modica P. Creatine supplements show some sports benefit. Medical Tribune News Service. July 10, 1997. 9. Vandenberghe K and others. Caffeine counteracts the ergogenic action of muscle creatine loading. Journal of Applied Physiology 80:452-457, 1996. 10. Volek JS and others. Creatine supplementation enhances muscular performance during high-intensity resistance exercise. Journal of American Dietetic Association 97:765-770, 1997. 11. Vandenberghe K and others. Long-term creatine intake is beneficial to muscle performance during resistance training. Journal of Applied Physiology 83:2055-2063, 1997. 12. Bosco C and others. Effect of oral creatine supplementation on jumping and running performance. International Journal of Sports Medicine 18:369-372, 1997. 13. Prevost MC, Nelson AG, Morris GS. Creatine supplementation enhances intermittent work performance. Research Quarterly for Exercise and Sport 68:233-240, 1997. 14. Casey A and others. Creatine ingestion favorably affects performance and muscle metabolism during maximal exercise in humans. American Journal of Physiology 271(1):E31-E37, 1996. 15. Volek JS and others. Performance and muscle fiber adaptations to creatine supplementation and heavy resistance training. Medicine and Science in Sports and Exercise 31:1147-1156, 1999. 16. Dawson B and others. Effects of oral creatine loading on single and repeated maximal short sprints. Australian Journal of Science and Medicine in Sport 27(3):56-61,1995. 17. Cooke WH, Grandjean PW, Barnes WS. Effect of oral creatine supplementation on power output and fatigue during bicycle ergometry. Journal of Applied Physiology 78:670-673, 1995. 18. Odland LM and others. Effect of oral creatine supplementation on muscle [Pcr] and short-term maximum power output. Medicine and Science in Sports and Exercise 29:216-219, 1997. 19. Snow RJ and others. Effect of creatine supplementation on sprint exercise performance and muscle metabolism Journal of Applied Physiology 84:1667-1673, 1998. 20. Tarnopolsky M. Creatine monohydrate increases strength in patients with neuromuscular diseases. Neurology 52:854-857, 1999. 21. Sorgen C. Creatine supplementation: The quest for power performance. Today's Dietitian (1)3:26-29, 1999. 22. FDA Special Nutritionals Adverse Event Monitoring System. Accessed June 7, 1999. 23 Juhn MS and others. Oral creatine supplementation in male collegiate athletes: A survey of dosing habits and side effects. Journal of the American Dietetic Association 99:593-594, 1999.